MANAJEMEN PENGEMBANGAN SDM UNTUK MENINGKATKAN MUTU DAYA SAING SEKOLAH DI SDN ULU BENTENG 2 KECAMATAN MARABAHAN - Monalisa Monalisa; Husnul Madihah; Jarkawi Jarkawi (LPPM Institut Pendidikan Nusantara Global, 2023)
The purpose of this study was to determine the planning, organizing, implementing and supervising human resource development programs to improve the quality and competitiveness of schools at SDN Ulu Benteng 2, Marabahan District.The theory used in this research is George R Terry's theory. Methodology This research uses a qualitative approach and this type of research uses qualitative descriptive research. Data collection techniques through observation, interviews, and documentation. Research Results: 1) planning the HR Development program, schools are able to formulate a strategy to develop quality teacher resources by involving teachers in professionalism development activities, and creating a planning document known as the School Work Plan (RKS). 2) Organizing the HR Development program, the principal has given clear job descriptions to teachers according to the abilities, skills and achievements of teachers in the form of a Principal's Decree which must be implemented by all teachers. 3) Implementation of the HR development program the head of SDN Ulu Benteng 2 involves teachers in professionalism development activities, such as KKG, workshops, IHT, seminars and conducting research, 4) Supervision of the HR development program is carried out through school supervision. The conclusion of this research is to develop human resources in accordance with planning, organizing, implementing and supervising, schools can provide training and professional development to their teachers. This can improve their competence and teaching skills, which in turn will improve the quality and competitiveness of their schools.